CORRELATION RADIO RANGEFINDER WITH NOISE-LIKE MODULATION OF THE SOUNDING SIGNAL - Prokopenko, Igor; Ilin, Oleksandr (Science-based technologies, 2025)
The article considers the correlation radar method of measuring the distance. It is noted that the development and research of new high-precision methods of measuring the distance is an urgent task, since modern aviation navigation and automatic flight control systems require accurate data on the height and distance to objects. Minimizing errors in measuring the distance, especially at low altitudes, is key to safe and accurate landing of aircraft, since even minor errors can lead to accidents. Increasing the accuracy of measurements not only reduces the risk of incorrect distance estimates, but also significantly increases flight safety. Measuring the distance in real conditions is complicated by the influence of obstacles and noise. Accurate measurements help compensate for these negative effects, ensuring correct recognition of objects and distances to them even under adverse conditions. In addition, increasing accuracy expands automation capabilities, reduces the impact of the human factor, and allows the use of modern data processing methods, the effectiveness of which is sensitive to the accuracy of the initial data. The basic principles of radio rangefinders are considered, namely measuring the range and speed of objects using radio waves. The calculation of the range is reduced to determining the time delay between the moment of emission of the sounding signal and the moment of reception of the signal reflected from the object. The calculation of the speed is reduced to determining the Doppler frequency shift. The article describes the main methods of measuring the distance, namely: pulse, phase and frequency. The pulse method is based on measuring the delay time of the reflected pulse. The phase method is based on determining the distance by the phase difference of the emitted and reflected signals. The basis of the frequency method is the use of periodic frequency modulation and determining the signal frequency gain. Structural schemes that implement these methods are considered. Their principles of operation are described by mathematical formulas and graphs, and significant shortcomings inherent in the considered methods are noted. In order to increase the accuracy of range measurement, a range measurement method based on correlation processing of a broadband signal with noise-like modulation is proposed. A structural diagram of a radio rangefinder that implements this method is presented. Using mathematical formulas and function graphs, the principle of operation of the scheme is considered in detail. In addition, the article notes that using the presented scheme, it is also possible to calculate the speed of the observed object. The corresponding formulas and calculations are given. The article proves that the introduction of the correlation method into range measurement complexes allows to significantly increase their accuracy and resolution.